2.46 ghz helical antenna design for wimax and wifi application / Dayang Suhaida Awang Damit, Samihah Abdullah and Rohaiza Baharudin - Awang Damit, Dayang Suhaida; Abdullah, Samihah; Baharudin, Rohaiza (Research Management Institute (RMI), 2013)
This project is to focus on to design of the basic geometry of helical antenna in small size at frequency 2.46 GHz. Several parameters dimensions and helical profiles were studied in order to obtain a suitable frequency range. The software that was applied for this simulation is the CST Microwave Studio (CST MWS) which is analytical tool that provides an accurate 3D EM simulation results for high frequency designs. From the simulation designs, the return losses were obtained. There were less than -23.9 dB. The results conclude that the helical antenna performed the properties of the 2.46 GHz frequency range. The simulation results obtained were S parameter, farfield, bandwidth and gain of the antenna. The measurement result shown that there was a slightly differences between the simulation results and measurement results. In a nutshell, all the results of revealed that the designed helical antenna performed at 2.46 GHz (Ultra High Frequency (UHF). At this 2.46 GHz can be applied to serve for a number of wireless applications including for WiMAX (Worldwide Interoperability for microwave Access) technologies.